Abnormalities of the Amygdala in schizophrenia: a real world study - Guangen Zheng; Yang Zhou; Jieming Zhou; Shuting Liang; Xiaoling Li; Caixia Xu; Guojun Xie; Jiaquan Liang (BMC Psychiatry, 2023)
Abstract Background Amygdala plays an important role in schizophrenia (SC), but its mechanisms are still unclear. Therefore, we investigated the relationship between the resting-state magnetic resonance imaging (rsMRI) signals of the amygdala and cognitive functions, providing references for future research in this area. Methods We collected 40 drug-naïve SC patients and 33 healthy controls (HC) from the Third People’s Hospital of Foshan. We used rsMRI and the automatic segmentation tool to extract the structural volume and local neural activity values of the amygdala and conducted Pearson correlation analysis with the Positive and Negative Syndrome Scale (PANSS) and the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) scores. Finally, we compared the clinical data, as well as the volume and functional changes of the amygdala in SC patients before and after treatment. Results Compared with HC, SC had widespread cognitive impairments, significant abnormalities in left amygdala function, while the reduction in volume of SC was not significant. Further Pearson correlation analysis with Bonferroni correction showed that only Immediate memory (learning) was significantly negatively correlated with fractional amplitude of low-frequency fluctuation (FALFF, r = -0.343, p = 0.001, p’ = 0.014 (Bonferroni correction)). When compared and analyzed the data difference of SC before and after treatment, we found that immediate memory and delayed memory of SC showed varying degrees of recovery after treatment (tlearning = -2.641, plearning = 0.011; tstory memory = -3.349, pstory memory = 0.001; tlist recall = -2.071, plist recall = 0.043; tstory recall = -2.424, pstory recall = 0.018). But the brain structure and function did not recover. Conclusion There was significant dysfunction in the amygdala in SC, and after conventional treatment, the function of the amygdala did not improve with the improvement of clinical symptoms and cognitive function.